Space jam - Benvenuti, Leo.; Reitman, Ivan.; Pytka, Joe.; Jordan, Michael, 1963-; Knight, Wayne; Randle, Theresa, 1967-; Murray, Bill, 1950 September 21-; West, Billy; DeVito, Danny; LaMarche, Maurice, 1958-; Bergen, Bob.; Warner Bros. Pictures (1969- ) (Burbank, CA : Distributed by Warner Home Video, 2010)
Michael Jordan is "recruited" from his baseball team to help the Warner Bros. characters defeat a group of aliens in a basketball game where the stakes are their freedom for all time.
Originally released as a motion picture in 1996.
Special features: commentary by Bugs Bunny, Daffy Duck and director Joe Pytka; production notes.
Michael Jordan, Wayne Knight, Theresa Randle, Bill Murray.
Voices: Billy West, Danny DeVito, Bob Bergen, Maurice LaMarche.
MPAA rating: PG.
DVD; region 1, NTSC; widescreen version, enhanced for widescreen TVs; Dolby digital 5.1 surround sound; dual layer.
Keywords: Cartoon characters -- Juvenile drama; Basketball players -- Juvenile drama; Comedy films; Live-action/animation films; Feature films